(untitled) (Journal of the College of Basic Education, 2022)
The modern poetic text has not been subjected to such a massive exposure World War II script dominance The dominance of the narration at the joints of most of the texts of his poets, until those texts became permissible spaces In which the narration reaches and wanders, and it seems that the modern poet abandoned lyricism and turned to other approaches Such as romanticism, realism, and symbolism did not prevent the emergence of another form, seeking help this time you lyrical wa With the capabilities of the narration to confuse or spread a thick fog that prevents his poetry from being stigmatized by lyricism, especially that The phenomenon of poetic narration is entirely a subjective lyrical phenomenon, except for the rare experiences of poets in their texts Narratives such as al-Sayyab, al-Malaikah, Baland, al-Bayati, and those who came to them from the poets or those who came after them, are only evidence of What we say, and from here we can prove the phenomenon of narrative hegemony over the modern poetic text, that hegemony